Queueing theory based accelerated traffic discharging model in front of emergency vehicle on intersection. (17th May 2019) - Sumaryo, Sony; Halim, Abdul; Ramli, Kalamullah; Joelianto, Endra
Intelligent Transportation System (ITS) is the integration between communication networks, real-time control, and information technology. The system is expected to perform more complex traffic arrangements, in particular traffic management of emergency vehicles. Implementation with traffic signal pre-emption alone is not enough to give space for the emergency vehicle to cross an intersection safely, especially if the lane street has only one lane. The paper proposes a new model of traffic discharge acceleration based on queueing theory approach. In the proposed model, two performance indicators are introduced which are: speed of normal traffic in front of the emergency vehicle and travelling time of the emergency vehicle. The aim is that the emergency vehicle could reach a destination within a certain time and a constant speed. Moreover, the delay should be managed to a minimum. Linear and exponential acceleration formulas of the traffic in front of the emergency vehicle are derived and then validated. Performances of the model are tested against the models in the literature. Simulation results show the proposed model leads to better assurance that emergency vehicle is not delayed significantly. Based on the validation test, a formula has also been developed according to the proposed model.